Musical Contention and Contentious Music; or, the Drums of Occupy Wall Street. Issue 5 (2nd November 2018) - Drott, Eric
Abstract : This paper addresses music's role in social movements, using work in mediation, assemblage, and actor-network theories to address the complex, contradictory, and contentious status that music often assumes within political protest. Three premises guide the discussion. First, if music is multiply mediated, then it follows that music's mediation of other activities (including protest) is likewise multiple. Second, this constellation of mediations may be productively conceptualised as an assemblage, with music forming part of movement-assemblages, and movements forming part of musical assemblages. Third, this mutual imbrication of musical and political assemblages—and the reversibility of positions it entails—introduces a source of potential friction. To illustrate these points, the second part of the article examines the controversies surrounding the drum circle that animated Liberty Park during the Occupy Wall Street protests of 2011.